O plano diretor de Farroupilha e os instrumentos aplicados ao desenvolvimento sustentável - Ferraro, Ricardo Moraes (My University, 2026)
The dissertation analyzes the instruments of Urban Law aimed at the sustainable development of cities, with a central focus on the Master Plan as the basic instrument of urban policy, as provided for in the Federal Constitution and the City Statute (Law No. 10,257/2001). The study seeks to understand how such instruments can be applied in urban planning in order to promote a balanced territorial management between the natural environment and the built environment. To this end, the municipality of Farroupilha/RS is adopted as a case study, whose urban legislation underwent a recent revision process, culminating in the enactment of a new Master Plan in January 2024. The research initially develops the conceptual, historical, and legal foundations of the master plan within the context of urban and environmental law, addressing the formation of urbanization, the need for land-use regulation, and the fundamental principles guiding urban policy. In this context, the work highlights the role of the master plan as the central normative instrument of municipal territorial planning, responsible for locally implementing the constitutional and legal guidelines related to the social function of the city and of property. Subsequently, the urban instruments selected for the research are analyzed: environmental zoning, the onerous grant of the right to build, the permeability rate, and policies of centralities and urban decentralization. These instruments are first examined based on the 2015 Master Plan, through an analysis of how they were regulated and their effective applicability within the territory of Farroupilha during its period of validity. The diagnostic assessment identifies normative advances, especially in the creation of specific environmental zoning categories and in the provision of instruments aimed at protecting sensitive areas, such as water resources, cultural heritage, and the natural environment. However, the study points to the existence of structural problems, notably the absence of a clear hierarchy of building indices according to the primary vocation of each zone, which compromised the practical effectiveness of the instruments. The dissertation demonstrates that environmental zoning plays a central role in the functioning of the municipal urban system, directly influencing the effectiveness of the other instruments analyzed. Weaknesses in the definition and application of urban parameters negatively affected the implementation of the onerous grant of the right to build, the protection of soil permeability, and the realization of decentralization policies and the creation of urban centralities. Finally, the work analyzes the 2024 Master Plan, highlighting the normative changes proposed to overcome the shortcomings identified in the previous plan. It emphasizes the adoption of a more coherent distribution of urban parameters according to the vocation of each zone and the consolidation of urban regimes in normative annexes, aiming to enhance legal certainty and reduce administrative discretion. It is concluded that the reorganization of urban planning parameters according to the territorial vocation of each zone, together with the enhanced normative systematization - particularly regarding the four instruments analyzed - introduced by the current Master Plan has strengthened legal certainty and the practical effectiveness of these instruments. This demonstrates that territorial planning, when legally structured and technically grounded, constitutes an essential tool for promoting sustainable development at the municipal level. [resumo fornecido pelo autor]
A dissertação tem como objeto a análise dos instrumentos do Direito Urbanístico voltados ao desenvolvimento sustentável das cidades, com enfoque central no Plano Diretor enquanto instrumento básico da política urbana, conforme previsto na Constituição Federal e no Estatuto da Cidade (Lei nº 10.257/2001). O estudo busca compreender de que forma tais instrumentos podem ser aplicados no planejamento urbano para promover uma gestão territorial equilibrada entre o meio ambiente natural e o meio ambiente construído. Para tanto, adota-se como estudo de caso o município de Farroupilha/RS, cuja legislação urbanística passou por recente processo de revisão, culminando na promulgação de um novo Plano Diretor em janeiro de 2024. A pesquisa desenvolve inicialmente os fundamentos conceituais, históricos e jurídicos do plano diretor no contexto do direito urbanístico e ambiental, abordando a formação da urbanização, a necessidade de regulação do uso do solo e os princípios fundamentais que orientam a política urbana. Nesse contexto, o trabalho destaca o papel do plano diretor como instrumento normativo central do ordenamento territorial municipal, responsável por concretizar localmente as diretrizes constitucionais e legais relativas à função social da cidade e da propriedade. Na sequência, são analisados os instrumentos urbanísticos selecionados para a pesquisa: o zoneamento ambiental, a outorga onerosa do direito de construir, a taxa de permeabilidade e as políticas de centralidades e descentralização urbana. Esses instrumentos são examinados, inicialmente, a partir do Plano Diretor de 2015, com análise da forma como foram normatizados e da sua efetiva aplicabilidade no território de Farroupilha ao longo de sua vigência. O diagnóstico realizado identifica avanços normativos, especialmente na criação de zoneamentos ambientais específicos e na previsão de instrumentos voltados à proteção de áreas sensíveis, como recursos hídricos, patrimônio cultural e meio ambiente natural. Contudo, aponta-se a existência de problemas estruturais, notadamente a ausência de hierarquização clara dos índices construtivos de acordo com a vocação principal de cada zona, o que comprometeu a eficácia prática dos instrumentos. O trabalho demonstra que o zoneamento ambiental exerce papel central no funcionamento do sistema urbanístico municipal, influenciando diretamente a efetividade dos demais instrumentos analisados. A fragilidade na definição e aplicação dos parâmetros urbanísticos repercutiu negativamente na implementação da outorga onerosa, na proteção da permeabilidade do solo e na concretização das políticas de descentralização e criação de centralidades urbanas. Por fim, o trabalho analisa o Plano Diretor de 2024, destacando as alterações normativas propostas com o objetivo de superar as lacunas identificadas no plano anterior. Evidencia-se a adoção de uma distribuição mais coerente dos parâmetros urbanísticos conforme a vocação das zonas e a consolidação dos regimes urbanísticos em anexos normativos, visando ampliar a segurança jurídica e reduzir a discricionariedade administrativa. Conclui-se que a reorganização dos parâmetros urbanísticos conforme a vocação territorial das zonas e a maior sistematização normativa, com destaque para os quatro instrumentos trabalhados, promovida pelo plano vigente ampliam a segurança jurídica e a efetividade prática dos instrumentos, demonstrando que o planejamento territorial, quando juridicamente estruturado e tecnicamente fundamentado, constitui ferramenta essencial para a promoção do desenvolvimento sustentável no âmbito municipal. [resumo fornecido pelo autor]
Keywords: Direito Urbanístico; Planejamento urbano; Desenvolvimento sustentável; Política urbana; Cidades e vilas - Farroupilha (RS) - Aspectos jurídicos; City planning and redevelopment law; City planning; Sustainable development; Urban policy; Cities and towns - Farroupilha (Brazil) - Legal aspects